Upper and lower genital tract Zika virus screening in a large cohort of reproductive-age women during the Americas epidemic. Issue 4 (October 2019) - Prisant, Nadia; Joguet, Guillaume; Moriniere, Catherine; Pavili, Lynda; Lurel, Sylvia; Herrmann-Stock, Cecile; Bujan, Louis
Abstract: Research question: To determine whether there is a risk of localized Zika virus (ZIKV) infection in the upper genital tract, specifically the oocytes, follicular fluids and endometrium, in exposed and/or recently infected reproductive-age women. ZIKV is an Aedes mosquito-borne Flavivirus that can lead to birth defects and to developmental anomalies when it infects pregnant women. Design: Controlled observational clinical study following 179 female patients undergoing oocyte vitrification cycles in an academic fertility centre during the ZIKV epidemic in the French territories of the Americas. At the time, the French Ministry of Health issued a ban on medically-induced pregnancies. Oocyte vitrification cycles were the only means of preserving fertility options and ensuring Zika-free oocyte cryopreservation for currently exposed and/or recently infected patients. Samples of serum, urine, lower genital tract, endometrium, follicular fluid and immature oocytes were tested for ZIKV RNA (vRNA) by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Serological analysis for ZIKV antibodies was performed in succession for the duration of the study. The follow-up protocol was set up for more than 6 months post-exposure or post-onset. Results: No vRNA was detected in the various samples from exposed patients. Furthermore, no vRNA was found in the upper genital tracts of women with a recent (3 months) history of acute infection. Conclusion: These findings represent evidence of a lack of vRNA persistence in the reproductive tract in ZIKV exposed and/or recently infected reproductive-age women and could help simplify current guidelines.